1985
DOI: 10.1016/0273-1177(85)90203-0
|View full text |Cite
|
Sign up to set email alerts
|

The Venus ionosphere

Abstract: Physical properties of the Venus ionosphere obtained by experiments on the US Pioneer Venus and the Soviet Venera missions are presented in the form of models suitable for inclusion in the Venus International Reference Atmosphere. The models comprise electron density (from 120 km), electron and ion temperatures, and relative ion abundance in the altitude range from 150 km to 1000 km for solar zenith angles from 0°to 1800. In addition, information on ion transport velocities, ionopause altitudes, and magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…The results of the simulations suggest that several mechanisms can explain the observed intensity of the green-line in the nightside of Venus, namely the Barth, and the controversial Frederick/Kopp mechanisms. In this latter case, the variations of the O + 2 density (Bauer et al 1985;Miller & Whitten 1991) could also explain the observed intensity fluctuations. Coordinated measurements from orbiting spacecraft, and Earthbased observatories, of both O + 2 density and green-line intensity, on the nightside ionosphere of Venus, are however necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…The results of the simulations suggest that several mechanisms can explain the observed intensity of the green-line in the nightside of Venus, namely the Barth, and the controversial Frederick/Kopp mechanisms. In this latter case, the variations of the O + 2 density (Bauer et al 1985;Miller & Whitten 1991) could also explain the observed intensity fluctuations. Coordinated measurements from orbiting spacecraft, and Earthbased observatories, of both O + 2 density and green-line intensity, on the nightside ionosphere of Venus, are however necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…Such small values of T e are difficult to reconcile, however, with the nearly SZA invariant median values of T e measured by the PV Langmuir probe near 147.5 km of ∼940 K presented by Theis et al [1984; see also Theis et al , 1980], or that from the PV RPA data, [ Miller et al , 1980], which showed a sharp increase in the altitude profile of the median values of T e near periapsis that was largely SZA invariant. The average electron temperatures at 150 km in the 80–90 and 90–100° SZA ranges are 800 and 1000 K, respectively, according the Venus International Reference Ionosphere [ Bauer et al , 1985].…”
Section: Resultsmentioning
confidence: 99%
“…There are only a few studies of T e as a function of SZA. In fact it appears that the median altitude profiles of T e are nearly SZA invariant [ Miller et al , 1980; Theis et al , 1980, 1984; Bauer et al , 1985].…”
Section: Discussionmentioning
confidence: 99%
“…For SZAs near and beyond about 145°, T i increases significantly and exceeds T e at high altitudes due to the formation of a shock as the nightward flowing ions become supersonic and their kinetic energy is transformed into thermal energy (e.g., Knudsen et al, 1981;Knudsen, 1992;Nagy et al, 1991). For an SZA of 145°, we adopt the values of T i from the VIRA model (Bauer et al, 1985). The T e and T i profiles were obtained for the 155°and 165°SZA models by adding at each altitude the difference between the neutral temperature and that for the 145°SZA model to the value of T i for the 145°model.…”
Section: Modelsmentioning
confidence: 99%
“…The electron temperatures in the Venus nightside ionosphere at high solar activity have been measured by the Pioneer Venus (PV) Orbiter Langmuir Probe (OETP) and by the retarding potential analyzer (ORPA), and have been found not to vary much over the nightside (e.g., Miller et al, 1980). At low altitudes we expect the values of T e to be thermalized with the neutral temperatures, but they may reach values of up to about 3000 K at 250 km, and about 5000 K near 800 km (e.g., Bauer et al, 1985).…”
Section: Introductionmentioning
confidence: 98%